Agronomic assessment of two populations of intermediate wheatgrass—Kernza® (Thinopyrum intermedium) in temperate South America. Issue 4 (8th January 2023) - Locatelli, Andres; Gutierrez, Lucia; Duchene, Olivier; Speranza, Pablo R.; Picasso Risso, Valentin D.
Abstract: Background: Kernza® intermediate wheatgrass is a perennial grain and forage crop that can provide several ecosystem services. Major research efforts focused on Kernza have taken place in high latitudes. The goal of this study was to evaluate, for the first time, the agronomic performance of Kernza in a low‐latitude region with mild winters. Methods: A KS‐cycle 4 Kernza population (A) was planted in spring in Wisconsin, USA, and selected in one cycle for lower vernalization requirements, obtaining a new population (B). These two populations, at three nitrogen (N) fertilization rates, were evaluated in a full factorial, completely randomized field experiment in Uruguay over 2 years. Results: The populations were similar in grain yields and flowering time in the 1st year, but population B had 63% lower grain yield in the 2nd year and 20% lower forage yield throughout the experiment. Increasing the N rate to 160 kg ha −1 led to a 63% increase in grain yield and 28% increase in forage yield across populations. Forage yields and nutritive values were similar to those reported in the northern hemisphere. However, grain yields for both the 1st (316 kg ha −1 ) and 2nd year (41 kg ha −1 ) were lower due to reduced flowering and weed competition. Conclusions: Expansion of Kernza to lower‐latitude regions will require further breeding to improve reproductive performance. Abstract : Kernza® is a dual‐purpose (grain and forage) perennial crop developed in high latitudes. In a field experiment carried out in a low‐latitude region, high forage yields and high nutritive value were obtained, but grain yields were low, possibly because the vernalization requirements of the species were not completely fulfilled.